Review of human joint monitoring devices: conventional vs. Optical fibre based sensors - G. M., Salim; Mohd Anwar, Zawawi (IOP Publishing, 2020)
Health monitoring devices are highly demanded in order to determine patients’ health condition, to monitor the health recovery progress, and to help the physiotherapist during rehabilitation period of a patient. This paper is focused on knee joint assessment devices and technology implementation. Knee joint angle measurement devices includes many devices such as accelerometer, electro-goniometer, torsiometer, acoustic, visual sensory, and optic fibre. There are several limitations to these technologies which require improvements. Many of the existing techniques and technologies are becoming conventional and there is a need to identify and to explore better methods to enhance the limitations of existing devices. The need of technologies with higher accuracy, reliability, and lower cost have always been a crucial factor. In this paper, a study of conventional and latest technologies are reviewed, and suggested to further explore the implementation of optical fibre based technology for the above-mentioned application. Optical fibre device has faster response, better accuracy, lighter in weight, lower cost, and is not effected by external physical variable such as electromagnetic waves as compared to conventional sensors.